The Impact of Programmed Cell Death on the Formation of Tertiary Lymphoid Structures - Dieudé, Mélanie; Kaci, Imane; Hébert, Marie-Josée (Frontiers in Immunology, 2021)
Tertiary lymphoid structures are clusters of lymphoid tissue that develop post-natally at sites of chronic inflammation. They have been described in association with infection, autoimmune disorders, cancer and allograft rejection. In their mature stage, TLS function as ectopic germinal centers, favoring the local production of autoantibodies and cytokines. TLS formation tends to parallel the severity of tissue injury and they are usually indicative of locally active immune responses. The presence of TLS in patients with solid tumors is usually associated with a better prognosis whereas their presence predicts increased maladaptive immunologic activity in patients with autoimmune disorders or allograft transplantation. Recent data highlight a correlation between active cell death and TLS formation and maturation. Our group recently identified apoptotic exosome-like vesicles, released by apoptotic cells, as novel inducers of TLS formation. Here, we review mechanisms of TLS formation and maturation with a specific focus on the emerging importance of tissue injury, programmed cell death and extracellular vesicles in TLS biogenesis.